Does Unemployment Affect Migration? Evidence from Micro Data - DaVanzo, Julie (The Review of Economics and Statistics, 1978)
Migration is a means of improving the allocation of human resources. People living in places where they are not fully employed or most highly valued are expected to move to destinations having brighter prospects but both policymakers and migration analysts seem to have mixed opinions as to whether private market forces alone are sufficient to induce them to do so. On the one hand there has been considerable discussion of policies (e.g. relocation assistance programs) designed to affect migration directly by enabling or inducing the unemployed to move to more promising labor markets the implication being that the unemployed are not themselves sufficiently responsive to economic conditions. On the other hand policies of investment in depressed areas are based largely on the premise that expanded local economic opportunities will reduce economically forced outmigration. Available evidence has provided little guidance to policymakers and others concerned with the influence of personal and area unemployment on outmigration. Several studies using survey data (e.g. Saben 1964; Lansing and Mueller 1967) have confirmed that certain unemployed workers are more likely to migrate than employed workers; but because these studies do not use adequate controls for other characteristics that may affect migration the direct contribution of unemployment to migration cannot be determined. Studies using aggregate data to assess the relationship between unemployment and migration (e.g. Lowry 1966) have obtained mixed results but unemployment is often measured at the end of the migration period an hence may have been affected by the intervening migration. (excerpt)